Morphometric, molecular characterization and management of Callosobruchus chinensis - SINGH, D; BOOPATHI, T (The Indian Journal of Agricultural Sciences, 2022)
Pulse beetle, Callosobruchus chinensis L. (Coleoptera: Chrysomelidae) is the most economic insect pest of pulse and can cause huge quantitative losses and also decreases the nutritional value of stored products. The morphological and molecular characterization of pulse beetles was determined and different non-edible oils against C. chinensis were assessed at ICAR-National Bureau of Plant Genetic Resources, New Delhi during 2019–20. Eggs of C. chinensis were 264.74±3.716 μm in width and 452.33±4.531 μm in length. The final instar larva of C. chinensis was 1703.12±4.692 μm in width and 3062.19±33.119 μm in length. The width and length of the pupae was 1696.09±5.589 μm and 3281.60±73.641 μm, respectively. The length of the adult body was 2520.85±23.278 μm for females and 2469.70±29.570 μm for males with a width of 1426.78±41.334 μm for females and 1456.54±23.606 μm for males. Both C. maculatus and C. chinensis got amplified by COI primer. A band of approximately 710 bp was obtained from both pulse beetles (C. maculatus and C. chinensis). DNA barcode helps in identification of pests at all life stages. Hundred per cent of egg mortality, larval mortality and adult mortality were reported in all non-edible oils such as Pongamia glabra L., Hydnocarpus wightiana Blume, Madhuca longifolia Konig, Callophyllum inophyllum L. and Azadirachta indica A. Juss. Similarly, all non-edible oils had ovipositional deterrence. To summarize, these oils can be used for the management of pulse beetles during storage.